Exploring Students’ Perception of Quizizz as a Learning Media in Higher Education - Sitompul, Harun; Sayekti, Retno; Saragih, Sri Rahmah Dewi (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2023)
The use of game in education has been evidenced to improve students’ engagement in learning. However, much research shows that the use of game in learning is only effective for high school students, while its use for students of higher education is limited. Research on game in education has predominantly been occupied by Kahoot! while Quizizz has received less analysis. This research aims to explore student perception of Quizizz as a learning media and the related obstacles experienced in a library science study program of State Islamic University of North Sumatera in Indonesia. The research uses a combination of quantitative and qualitative methods, such as survey and focused group discussion, with a sample of 272 undergraduate students. The study found that the use of games in learning actively increased student engagement and led to a significant improvement in independence and self-control in learning. During the learning activity students maintain that they gain their self-confidence while enjoying the game. The research suggests that to increase learning achievement, educators should use various teaching strategies that encourage students’ active mental and physical engagement. Additionally, it is expected that this learning experience and content will enhance students' retentive memory.